The current status of behaviorism and neurofeedback. - Fultz DE (International Journal of Behavioral Consultation & Therapy, 2009)
There appears to be no dominant conceptual model for the process and outcomes of neurofeedback among practitioners or manufacturers. Behaviorists are well-positioned to develop a neuroscience-based source code in which neural activity is described in behavioral terms, providing a basis for behavioral conceptualization and education of neurofeedback providers and their clients.